Arthrocentesis and Temporomandibular Joint Disorders: Clinical and Radiological Results of a Prospective Study. (11th November 2013) - De Riu, Giacomo; Stimolo, Mirella; Meloni, Silvio Mario; Soma, Damiano; Pisano, Milena; Sembronio, Salvatore; Tullio, Antonio
Abstract : Purpose . We evaluated the efficacy of arthrocentesis in the treatment of temporomandibular joint (TMJ) disorders. Material and Methods . In this prospective clinical case series, 30 consecutive patients with TMJ disorders underwent arthrocentesis using saline and sodium hyaluronate injections. Outcome measures were TMJ pain, maximum mouth opening (MMO), joint noises, and anatomical changes in the TMJ architecture. Patients were evaluated using cone-beam computed tomography (CBCT) and magnetic resonance imaging (MRI) at the beginning of treatment and 60 days after the last arthrocentesis. Pretreatment and posttreatment clinical parameters were compared using paired and unpaired t -tests, and McNemar's test was used to evaluate CBCT and MRI changes (P < 0.05 ). Results . At 1-year follow-up examinations, visual analogue scale scores indicated that pain was reduced significantly and mean postoperative MMO was increased significantly. CBCT findings showed no significant change, and MRI showed only slight reductions in inflammatory signs. Conclusions . Within the limitations of this study, we can conclude that arthrocentesis is a simple, minimally invasive procedure with a relatively low risk of complications and significant clinical benefits in patients with TMJ disorders. This trial is registered with NCT01903512 .